2021
DOI: 10.3390/agronomy11061049
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of GhMPK3 from Cotton Enhances Cold, Drought, and Salt Stress in Arabidopsis

Abstract: Cotton production is hampered by a variety of abiotic stresses that wreak havoc on the growth and development of plants, resulting in significant financial losses. According to reports, cotton production areas have declined around the world as a result of the ongoing stress. Therefore, plant breeding programs are concentrating on abiotic stress-tolerant cotton varieties. Mitogen-activated protein kinase (MAPK) cascades are involved in plant growth, stress responses, and the hormonal signaling pathway. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 61 publications
2
13
0
Order By: Relevance
“…Under drought circumstances, the concentrations of oxidant (MDA and H 2 O 2 ) and antioxidant (CAT and POD) enzymes in GhMPK3 silenced, and WT plants were determined. The investigation revealed that antioxidant concentrations were much lower in the silenced plants, whereas oxidant levels increased dramatically when compared with the control plants ( Yang et al, 2019 ; Kirungu et al, 2020 ; Sadau et al, 2021 ). Moreover, GLKs confer biological stress resistance in crops.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Under drought circumstances, the concentrations of oxidant (MDA and H 2 O 2 ) and antioxidant (CAT and POD) enzymes in GhMPK3 silenced, and WT plants were determined. The investigation revealed that antioxidant concentrations were much lower in the silenced plants, whereas oxidant levels increased dramatically when compared with the control plants ( Yang et al, 2019 ; Kirungu et al, 2020 ; Sadau et al, 2021 ). Moreover, GLKs confer biological stress resistance in crops.…”
Section: Discussionmentioning
confidence: 94%
“…This indicates that the overexpressed gene has the potential to regulate abiotic stress tolerance. A report in stress-responsive genes investigated in transgenic lines of GhMPK3 showed upregulated expression compared with the WT ( Sadau et al, 2021 ). Therefore, current results propose that the GhGLK1 might be involved in regulating the genes that play a key role in drought and cold stress tolerance in cotton.…”
Section: Discussionmentioning
confidence: 99%
“…Under mannitol treatment, Gh_A06G1257 plants have higher antioxidants activities including CAT and Peroxidase (POD) whereas, lower activities of oxidant enzymes (MDA and H 2 O 2 ) than wild-type (WT) plants. Under stress treatment, GhMPK3 overexpressed plants were shown to have higher levels of antioxidants and lower contents of oxidant enzymes than WT plants (Sadau et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The seedlings were moved to a growing environment with a temperature of 25°C and a 16 light/8 dark hours cycle from the selection medium at three-leaf stages. The little plastic pots were filled with a 1:1 mix of vermiculite and humus (Sadau et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, GhMPK3 was identified and characterized from upland cotton. Silencing GhMPK3 increased drought tolerance in cotton plants, whereas overexpression improved plant resistance to drought, cold, and salt stress ( Sadau et al, 2021 ). These findings help in better understanding of the regulatory network of MAPKs under salt and drought stresses, and offer another strategy for improving stress tolerance in cotton crop production.…”
Section: Genes Involved In Response To Salt and Drought Stressmentioning
confidence: 99%